Use of Digital Health Information for Health Information Seeking Among Men Living With Chronic Disease: Data From the Health Information National Trends Survey. Issue 1 (January 2020) - Sherman, Ledric D.; Patterson, Megan S.; Tomar, Aditi; Wigfall, Lisa T.
Although diabetes education plays an important role in self-management for people living with diabetes, male health "help-seeking" lags far behind women. These gender-related "help-seeking" disparities often result in males being less engaged in their health care, which subsequently leads to poorer health outcomes among males. In this cross-sectional study, we used data from the 2017 Health Information National Trends Survey (HINTS) to identify factors that may contribute to communication inequalities between males and females. A hierarchical linear/logistic regression model was used to examine factors associated with online health information seeking among males living with diabetes. The results suggest that education, income, age, identifying as Hispanic, being a smoker, using a device to track progress toward a health-related goal, and using device to seek health information were all related to eHealth sum scores. Future research should consider testing applications among various at-risk groups to determine if the technology itself is becoming a barrier to eHealth.